Incessant cycles of dystrophic myofiber degeneration and regeneration result in ubiquitous centrally-nucleated fibers in skeletal muscles of X-chromosome-linked muscular dystrophy (mdx) mouse - Y. H. Saponjian (ՀՀ ԳԱԱ հրատ.)
Duchenne muscular dystrophy (DMD) is an X-linked recessive, degenerative disorder and is the most prevalent, devastating and fatal pediatric neuromuscular disorder in the world. DMD is primarily caused by loss-of-function mutations in the dystrophin gene that result in either partial and dysfunctional domains in dystrophin protein or complete absence of it, leading to contractioninduced necrosis of skeletal muscle fibers and eventual replacement with adipose and connective tissue. Ultimately, rapid and subjugating progression of myofiber degeneration and necrosis, along with gradual attenuation and failure of regenerative capacity, rather than failure of muscle development, result in the crippling phenotype of DMD. The X-chromosome-linked muscular dystrophy (mdx) mouse is genetically homologous to human DMD but exhibits a milder phenotype and evades severe end-stage histopathology. Histopathologic analysis revealed that skeletal muscles of mdx mice exhibit drastically elevated levels of centrally-nucleated myofibers, similar to humans with DMD, as a result of incessant cycles of dystrophic myofiber degeneration and regeneration. Դյուշենի մկանային դիստրոֆիան (ԴՄԴ) X–քրոմոսոմի հետ կապված ռեցեսիվ, դեգեներատիվ խանգարում է և աշխարհում ամենատարածված, ամենածանրընթաց ու ամենամահացու մանկական նյարդամկանային հիվանդությունն է: Դիստրոֆին գենի մուտացիաները բերում են դիստրոֆին պրոտեինի բացակայության կամ դիսֆունկցիայի, որը հանգեցնում է կմախքային մկանների մանրաթելերի կրճատմամբ պայմանավորված նեկրոզի և նրանց` ճարպային և շարակցական հյուսվածքներով փոխարինմանը: Ի վերջո, ԴՄԴ-ի անդամալույծ դարձնող բարդ ֆենոտիպը պայմանավորված է ոչ թե մկանների թերզարգացմամբ, այլ մկանների արագ զարգացող դեգեներացիայով, նեկրոզով և մկանների ռեգեներացիոն ունակության աստիճանական խախտմամբ: X-քրոմոսոմով պայմանավորված մկանային դիստրոֆիայով (mdx) մուկը գենետիկորեն համանման է մարդկային ԴՄԴ-ին, բայց ցուցաբերում է ավելի մեղմ ֆենոտիպ և շրջանցում է վերջին փուլին բնորոշ ծանր հիստոպաթոլոգիան: Հիստոպաթոլոգիական վերլուծությունը ցույց տվեց, որ mdx մկան կմախկային մկանները, ԴՄԴ-ով հիվանդ երեխաների մկանների նման, պարունակում են խիստ բարձր քանակով կենտրոնական կորիզով մանրաթելեր, ինչը վկայում է դիստրոֆիկ մկաններում անընդհատ կրկնվող դեգեներատիվ և ռեգեներատիվ ցիկլերի մասին: Мышечная дистрофия Дюшенна (МДД) является рецессивным дегенеративным расстройством, сцепленным с Х-хромосомой, и самым распространенным, тяжелотекущим и смертельным педиатрическим нервно-мышечным заболеванием в мире. При МДД мутации гена дистрофина приводят к частичной или полной дисфункции протеина дистрофина или к его отсутствию вообще, в результате чего развивается некроз волокон скелетных мышц, обусловленный их сокращением, и перерождение их в жировую и соединительную ткань. В итоге инвалидизирующий фенотип МДД обусловлен не недоразвитием мышц, а их быстропрогрессирующей дегенерацией и некрозом и постепенной потерей регенерационной способности мышц. Модель мыши с мышечной дистрофией, сцепленной с Х-хромосомой (mdx), генетически гомологична МДД человека, но проявляется менее выраженным фенотипом и обходит тяжелую гистопатологию, характерную для конечной стадии болезни. Гистопатологический анализ показал, что скелетные мышцы mdx мыши имеют резко повышенный уровень центральноядерных мышечных волокон, как и у больных МДД детей, что является результатом непрерывно повторяющихся циклов дегенерации и регенерации дистрофических мышечных волокон.
Keywords: Biology; Molecular Biology